Instability investigation of In0.7Ga0.3As quantum-well MOSFETs with Al2O3 and Al2O3/HfO2. (July 2016) - Kwon, Hyuk-Min; Kim, Do-Kywn; Lim, Sung-Kyu; Hwang, Hae-Chul; Son, Seung Woo; Park, Jung Ho; Park, Won-Sang; Kim, Jin Su; Shin, Chan-Soo; Park, Won-Kyu; Lee, Jung Hee; Kim, Taewoo; et al.
Highlights: We performed the instability investigation on InGaAs quantum-well InGaAs MOSFETs. The InGaAs MOSFET with Al2 O3 /HfO2 exhibits better electrostatic integrity, however, it shows worse reliability and frequency dispersion behavior than one with Al2 O3 . At cryogenic temperature, the device with Al2 O3 /HfO2 induces worse hysteresis behavior than one with Al2 O3 . Abstract: We present an instability investigation of In0.7 Ga0.3 As quantum-well (QW) metal–oxide–semiconductor field-effect-transistors (MOSFETs) on InP substrate with Al2 O3 and Al2 O3 /HfO2 gate stacks. The device with bi-layer Al2 O3 /HfO2 gate stack exhibits larger shift in threshold-voltage (Δ V T ) under a constant-voltage-stress condition (CVS), than one with single Al2 O3 gate stack. At cryogenic temperature, the device with bi-layer Al2 O3 /HfO2 gate stack also induces worse hysteresis behavior than one with single Al2 O3 gate stack. These are mainly attributed to more traps inside the HfO2 material, yielding a charge build-up inside the HfO2 gate dielectric. This strongly calls for a follow-up process to minimize those traps within the high- k dielectric layer and eventually to improve the reliability of InGaAs MOSFETs with HfO2 -based high- k gate dielectric.